"The C‐Word" Meets "the N‐Word": The Slur‐Once‐Removed and the Discursive Construction of "Reverse Racism". (1st August 2018) - Bax, Anna
Abstract : This article examines one strategy in the discursive construction of so‐called reverse racism: the slur‐once‐removed, a linguistic construction in the form the X‐word, used to euphemize slurs. Building on structural similarity to the N‐word, the C‐word has emerged as a euphemism for cracker . Using dialogic syntax and stance theory, the article analyzes media debates surrounding the George Zimmerman murder trial to argue that the parallelism of form between the C‐word and the N‐word constructs their referents as similarly harmful. Euphemizing cracker as the C‐word indexes cracker as a racist slur, and by extension discursively constructs the phenomenon of reverse racism.